Defining a novel leptin–melanocortin–kisspeptin pathway involved in the metabolic control of puberty - Manfredi-Lozano, Maria (Mol Metab, 2016)
OBJECTIVE: Puberty is a key developmental phenomenon highly sensitive to metabolic modulation. Worrying trends of changes in the timing of puberty have been reported in humans. These might be linked to the escalating prevalence of childhood obesity and could have deleterious impacts on later (cardio-metabolic) health, but their underlying mechanisms remain unsolved. The neuropeptide α-MSH, made by POMC neurons, plays a key role in energy homeostasis by mediating the actions of leptin and likely participates in the control of reproduction. However, its role in the metabolic regulation of puberty and interplay with kisspeptin, an essential puberty-regulating neuropeptide encoded by Kiss1, remain largely unknown. We aim here to unveil the potential contribution of central α-MSH signaling in the metabolic control of puberty by addressing its role in mediating the pubertal effects of leptin and its potential interaction with kisspeptin. METHODS: Using wild type and genetically modified rodent models, we implemented pharmacological studies, expression analyses, electrophysiological recordings, and virogenetic approaches involving DREADD technology to selectively inhibit Kiss1 neurons, in order to interrogate the physiological role of a putative leptin→α-MSH→kisspeptin pathway in the metabolic control of puberty. RESULTS: Stimulation of central α-MSH signaling robustly activated the reproductive axis in pubertal rats, whereas chronic inhibition of melanocortin receptors MC3/4R, delayed puberty, and prevented the permissive effect of leptin on puberty onset. Central blockade of MC3/4R or genetic elimination of kisspeptin receptors from POMC neurons did not affect kisspeptin effects. Conversely, congenital ablation of kisspeptin receptors or inducible, DREADD-mediated inhibition of arcuate nucleus (ARC) Kiss1 neurons resulted in markedly attenuated gonadotropic responses to MC3/4R activation. Furthermore, close appositions were observed between POMC fibers and ARC Kiss1 neurons while blockade of α-MSH signaling suppressed Kiss1 expression in the ARC of pubertal rats. CONCLUSIONS: Our physiological, virogenetic, and functional genomic studies document a novel α-MSH→kisspeptin→GnRH neuronal signaling pathway involved in transmitting the permissive effects of leptin on pubertal maturation, which is relevant for the metabolic (and, eventually, pharmacological) regulation of puberty onset.